The Effect Of Counseling On How To Care For Normal Newborn Babies At Home On Postage Mothers In Pmb Lusi Yuliani, Sudimoro Village, Megaluh Jombang District - Kiftiyah Kiftiyah; Nanik Nur Rosyidah; Nur Chasanah (Universitas Islam Lamongan, 2020)
Newborn care is caring for babies without the help of medical staff again starting out of hospitals, maternity clinics, health centers, for example, such as breastfeeding, the right position when breastfeeding, bathing the baby, caring for the baby's umbilical cord and keeping the baby healthy. The mother's skill in caring for her baby is very influential on the baby's health. In addition, baby care that is carried out directly by the mother will make the baby feel comfortable and can have a positive impact on the growth and development of the baby in the future. However, in reality, there are still many postpartum mothers who do not have good abilities and skills in caring for their babies (Priscilla, 2013). The aim of the study was to determine the effect of counseling on how to care for normal newborns at home for primiparous postpartum mothers in PMB Lusi Yuliani, Sudimoro Village, Subdistrict Megaluh, Jombang Regency. This research is a pra experimental design uses purposive random sampling technique. The population in this study were 20 postpartum mothers. The samples taken in the study were 15 postpartum mothers at PMB Lusi Yuliani, Sudimoro Village, Megaluh District. Based on the results of research in Sudimoro Village, Megaluh District, it can be concluded that almost half of the respondents are not skilled at caring for newborns at home. The results of the analysis test using the Wilcoxon sign rank test showed = 0.000 (α = 0.05). 66.7% of primiparous postpartum mothers were quite skilled and 33.3% were less skilled in caring for normal newborns before counseling. After counseling, 100% of primipara postpartum mothers were skilled in caring for normal newborns properly. Seeing from the results of the study, it was found that counseling had an effect on the behavior of how to care for newborns for primiparous postpartum mothers, so as a midwife it is expected to be able to develop midwifery services through counseling and counseling so that it can help increase the knowledge of mothers, especially primiparous postpartum mothers who have no experience in caring for newborns at home. .Keywords: Behavioral Counseling, How to Care for Newborns